Immediate and long‐term impact of the COVID‐19 pandemic on delivery of surgical services. Issue 10 (30th April 2020) - Søreide, K.; Hallet, J.; Matthews, J. B.; Schnitzbauer, A. A.; Line, P. D.; Lai, P. B. S.; Otero, J.; Callegaro, D.; Warner, S. G.; Baxter, N. N.; Teh, C. S. C.; Ng‐Kamstra, J.; et al.
Abstract : Background: The ongoing pandemic is having a collateral health effect on delivery of surgical care to millions of patients. Very little is known about pandemic management and effects on other services, including delivery of surgery. Methods: This was a scoping review of all available literature pertaining to COVID‐19 and surgery, using electronic databases, society websites, webinars and preprint repositories. Results: Several perioperative guidelines have been issued within a short time. Many suggestions are contradictory and based on anecdotal data at best. As regions with the highest volume of operations per capita are being hit, an unprecedented number of operations are being cancelled or deferred. No major stakeholder seems to have considered how a pandemic deprives patients with a surgical condition of resources, with patients disproportionally affected owing to the nature of treatment (use of anaesthesia, operating rooms, protective equipment, physical invasion and need for perioperative care). No recommendations exist regarding how to reopen surgical delivery. The postpandemic evaluation and future planning should involve surgical services as an essential part to maintain appropriate surgical care for the population during an outbreak. Surgical delivery, owing to its cross‐cutting nature and synergistic effects on health systems at large, needs to be built into the WHO agenda for national health planning. Conclusion: Patients are being deprived of surgical access, with uncertain loss of function and risk of adverse prognosis as a collateral effect of the pandemic. Surgical services need a contingency plan for maintaining surgical care in an ongoing or postpandemic phase. Abstract : Surgical services are adapting to mitigate the surge in patients with COVID‐19 in need of critical care support. All non‐essential elective surgery has been cancelled, or is pending cancellation, in healthcare systems around the globe, impacting millions of patients. The postpandemic phase will require re‐establishment of surgical services, and capacity building to restore normalcy and to appropriately reduce the backlog of cases by priority. A framework for evaluation and a plan to incorporate surgical care into the WHO strategies for national health plans and pandemic mitigation is urgently needed. Preparing for the next wave Abstract : Antecedentes: La pandemia en curso tiene un efecto colateral sobre la salud en la prestación de atención quirúrgica a millones de pacientes. Se sabe muy poco sobre el manejo de la pandemia y sus efectos colaterales en otros servicios, incluida la prestación de servicios quirúrgicos. Métodos: Se ha realizado una revisión de alcance de toda la literatura disponible relacionada con COVID‐19 y cirugía utilizando bases de datos electrónicas, páginas web de sociedades, seminarios online y repositorios de pre‐publicaciones. Resultados: Se han publicado varias guías perioperatorias en un corto período de tiempo. Muchas recomendaciones son contradictorias y, en el mejor de los casos, se basan en datos anecdóticos. A medida que las regiones con el mayor volumen de operaciones per cápita se ven afectadas, se cancela o difiere un número sin precedentes de operaciones. Ninguna de las principales partes interesadas parece haber considerado cómo una pandemia priva de recursos a los pacientes que necesitan una intervención quirúrgica, con pacientes afectados de manera desproporcionada debido a la naturaleza del tratamiento (uso de anestesia, quirófanos, equipo de protección, contacto físico y necesidad de atención perioperatoria). No existen recomendaciones sobre cómo reanudar la actividad quirúrgica. La evaluación tras la pandemia y la planificación futura deben incluir a los servicios quirúrgicos como una parte esencial para mantener la atención quirúrgica adecuada para la población también durante un brote epidémico. La prestación de servicios quirúrgicos, debido a su naturaleza transversal y a sus efectos sinérgicos en los sistemas de salud en general, debe incorporarse a la agenda de la OMS para la planificación nacional de la salud. Conclusión: Los pacientes se ven privados de acceso a la cirugía con una pérdida de función incierta y riesgo de un pronóstico adverso como efecto colateral de la pandemia. Los servicios quirúrgicos necesitan un plan de contingencia para mantener la atención quirúrgica durante la pandemia y en la fase post‐pandemia.